Critical Review of Vandhyatwa w.s.r. Anovulation - Literary review (International Journal of Ayurveda and Pharma Research, 2021)
Infertility is a condition which can be defined as inability to conceive with minimum one year of unprotected sexual life. There may be good number of reasons for this condition to cause. Inability of couples to fulfill their desire of continuing the family has been a social stigma since ages. Due to increasing publicity and awareness and also educational status of couple making them easy to seek help for the conception. The causes for this condition are problems in female and male reproductive system in structure and physiological function, psychology of couple, genetic, environmental, immunological and sometime unexplained causes also may account for this condition. Vandyatwa is a condition where a female fails to conceive and also unable to continue pregnancy and give a birth of a live baby and also unable to conceive in future. Ayurveda believes that the conception occurs only in Shudha Yoni.Methodology: To review, analyse and interpret about female Infertility, its types, causes, Anovulation as one of the causes of infertility, its types, interpretation and Ayurvedic understanding of anovulation as a cause of Vandyatwa. The integral part of achieving Sreyasi Praja are Garbhasambhava Samagri which includes Ritu, Kshetra, Ambu, Beeja. As there are many causes for Vandyatwa mentioned, in this study Vandyatwa due to Arthava Nasha or Nastartva is considered where Arthava is taken as ovum. Discussion- Infertility is observed in approximately 10-15% of couples of reproductive age. Ovulation disorders account for about 30-40% of female infertility and about 20% of infertility couple. Anovulation is caused due to the defect in the function of hypothalamus -pituitary- ovarian axis. Arthava is considered as ovum and it is formed as a Upadhatu after the proper digestion of Ahara Rasa by Prakrutha Agni. If Agni is disturbed by Ahita Ahara vihara formation of Rasadi Dhatu there by Arthava is also affected causing Nastartva which can be considered as anovulation.The condition Nastartva also can be managed by Deepana pachana and Arthava Janaka which is the line of management to correct the Samprapti and to restore fertility. Many Yogas are mentioned by our Acharya’s, & Pipplayadi Yoga which contains Trikatu and Nagakeshara is one among them mentioned in Bhaishajya Ratnavali Yonivyapath chikitsa for Vandyatwa.